The Geger Banten of 1888: An Anthropological Perspective of 19th Century Millenarianism in Indonesia - Dadi Darmadi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
This paper tries to analyse the millenarian response of the Bantenese to the Western colonization from an anthropological perspective. The history of Banten at the end of the 19th and beginning of the 20th century was marked by various indigenous unrest, rebellion, and resistance against the colonial power. In 1888, several religious leaders of Sufi brotherhoods and community leaders in Cilegon, Banten led a revolt against the Dutch colonial government. This uprising was provoked by the Dutch’s trade regulation, a new economic system, and was fuelled by enduring religious sentiments against the Dutch. While most scholars frame the event as a religious or social political movement, this study focuses on to what some of the Bantenese Muslims perceived as “unjust” social situations of the colonized world: poverty, inequality, religious restriction, social and political marginalization.